Spin-torque ferromagnetic resonance investigation for enhancement of spin-orbit torque efficiency - Wong, Grayson Dao Hwee (Nanyang Technological University, 2022)
Current-induced magnetization switching by spin-orbit torque generated through heavy metals offers an enticing realm for energy-efficient memory and logic devices. Since the first demonstration of the spin Hall effect, many research revolves about understanding and enhancing its efficiency. However, even with the accumulated development over the past decades, the techniques to enhance the spin current generation are limited while the manipulation of current-induced spin-orbit torques remains elusive and challenging. In our work, we explored the thermal behaviors of spin current generation in PtxCu1-x alloys in search for robustness even at elevated temperature. Next, we investigated the effects of strain on spin current generation and discovered that the enhancement can be retained. This enhancement can then be controlled using a combination of annealing and strain treatment. Our findings help deepen our understanding of the different techniques to manipulate the spin-current generation.